Cardiovascular Drug Interactions with Nirmatrelvir/Ritonavir for COVID-19: Considerations for Daily Practice - Andrea Di Lenarda; Nicola Ferri; Massimiliano Lanzafame; Eva Agostina Montuori; Luciano Pacelli (European Cardiology Review)
Cardiovascular disease is associated with progression to severe COVID-19 and patients with the condition are among those in whom early antiviral therapy should be warranted. The combination of nirmatrelvir/ritonavir (Paxlovid®) has been approved for clinical use by the Food and Drug Administration and European Medicines Agency. Because patients with cardiovascular disease are often on polypharmacy, physicians need to be aware of potential drug–drug interactions (DDIs) when treating COVID-19 with nirmatrelvir/ritonavir. Guidance is given for avoiding DDIs, emphasising that preventing and managing potential DDIs with nirmatrelvir/ritonavir requires thorough assessment and knowledge. The present review summarises the clinical pharmacology of nirmatrelvir/ritonavir and provides details on potential DDIs with a focus on daily practice in patients with cardiovascular disease. Particular attention is needed for drugs that are predominantly metabolised by cytochrome P450 3A4, are substrates of P-glycoprotein and have a narrow therapeutic index. Proper management of potential DDIs must balance the benefit of nirmatrelvir/ritonavir to prevent severe disease with the risk of serious adverse events.